ANALISIS HUBUNGAN LITERASI NUMERASI DAN HASIL BELAJAR SISWA - Ana Nursyifa; Siti Masyithoh (Jurnal Pendidikan Dasar dan Keguruan, 2023)
This article aims to determine the relationship between numeracy literacy and learning outcomes in schools, especially in elementary schools. The method used in this research is descriptive with a qualitative approach. The results of the study show that numeracy literacy has a relationship that influences each other on student learning outcomes, because with students understanding and being able to use skills in managing numbers and symbols properly, learning outcomes especially in mathematics can be further improved than before. In addition, numeracy literacy skills can also improve the ability to solve problems related to numbers, tables and symbols in everyday life. Thus, it can be concluded that numeracy literacy has a very influential relationship with student learning outcomes.